Effect of aerobic and resistance exercise programs on arterial stiffness, serum IL6 and IL10 in obese women - Ziba Rahimian Mashhad; Seyed Reza Attarzadeh Hosseini; Amir Rashid Lamir; Mohammad Ali Sardar; Sirous Nekooei; Ramesh Giti (Mashhad University of Medical Sciences, 2020)
Introduction: Nodaways, exercise and physical activities are used as effective non-pharmacological treatment to minimize arterial stiffness and prevent cardiovascular disease. This study was performed with aim to compare the effect of aerobic and resistance training on arterial stiffness, inflammatory and anti-inflammatory factors in obese sedentary women. Methods: This clinical trial study was performed in 2018 on 27 obese women with an age range of 30-40 years in Mashhad. The subjects were randomly assigned into two groups of aerobic and resistance training. Aerobic exercise was hold with an intensity of 50-70% of the maximum heart rate reserve and resistance exercise programs with 60-85% intensity of one repetition maximum for 24 sessions every other day. Blood samples were taken and maximal oxygen uptake and arterial stiffness were measured at the beginning of the 1th, 13th and 24th sessions. Data were analyzed by SPSS software (version 22) and repeated-measures ANOVA, Friedman and Tukey tests. P<0.05 was considered statistically significant. Results: Both aerobic and resistance exercise programs significantly increased maximal oxygen consumption, skeletal muscle mass and significantly decreased pulse pressure (p<0.05). The effect of aerobic exercise on oxygen uptake was more than resistance training (p=0.023), but there was no difference between the effect of both exercise programs on decreasing pulse pressure (p=0.879). Changes in IL6 and IL10 were not significant in both aerobic and resistance exercise programs (p>0.05). Conclusion: Both aerobic training and resistance exercise can have a positive impact on the structural properties of the artery wall of inactive obese women and can be used as a non-pharmacological treatment to minimize arterial stiffness and prevent cardiovascular disease.